Cardiovascular Disease Burden and Risk Factors Before and After Kidney Transplant - T. Keddis, Mira; Bhutani, Gauri; M. El-Zoghby, Ziad (Cardiovascular & Haematological Disorders - Drug Targets, 2014)
Cardiovascular (CV) disease is the most common cause of mortality among kidney transplant candidates on the waiting-list and after kidney transplantation. The mechanisms of cardiovascular disease burden after transplant are multifactorial and the risk is largely determined by pre-transplant factors including CV disease and dialysis duration. Current pre-transplant cardiac evaluation protocols have proven to be inconsistent in predicting adverse cardiovascular outcome post-transplant. However, multiple biomarkers have been recognized as predictors of all-cause mortality and cardiovascular events including graft function, hemoglobin, homocysteine, C - reactive protein among others. Of these, elevation in the biomarker cardiac troponin T appears to be a significant predictor of cardiovascular events and mortality among wait-listed kidney transplant candidates and after transplantation. The relationship between CV risk reduction, normalization of cardiac troponin T levels and restoration of renal function after kidney transplant is complex but opens opportunities for the use of cardiac troponin T and other cardiovascular biomarkers as important endpoints of clinical interventions in kidney transplant recipients.
Keywords: risk factors